Effective Marketing Strategies for a Medical Laboratory Science Program. - BEAZER, KENDAL; CUMMINS, KENTON (Clinical Laboratory Science)
The medical field is in dire need of more qualified medical laboratory scientists (MLSs) and medical laboratory technicians (MLTs). Medical laboratory educational programs are diminishing, and medical staff in hospitals are unaware of the unequivocal value trained lab scientists bring to the quality of their patients' lab results. The national need for more qualified laboratory testing personnel is outpacing the supply. A survey to determine current marketing trends and methods was sent out to 469 program directors of MLS and/or MLT programs, with a 35% response rate. Responses were compared with proven marketing methods to give marketing suggestions relevant to the MLS field. This paper describes the research in how MLS programs currently market themselves. Explanations of marketing techniques are discussed with the intent to help simplify marketing efforts for a more effective marketing strategy. This study showed that medical and clinical laboratory educational programs nationwide should increase marketing and promote the MLS value to local communities.